Promising Targets and Current Clinical Trials in Metastatic Squamous Cell Lung Cancer - Vincent, Mark D. (Frontiers in Oncology, 2014)
ABSTRACT Squamous cancer of the lung (SQCC), although no longer the premier variant of non-small cell lung cancer (NSCLC), continues to impose a heavy world-wide burden. Advanced SQCC has enjoyed little of the recent progress benefiting patients with adenocarcinoma of the lung (ADC), but that has now begun to change. This article reviews the underlying molecular pathology of SQCC, as well as potential new targets and the corresponding novel targeted agents; included are some of which may soon be approvable in this notoriously hard-to-treat indication.